PROTEINASE-INHIBITORY POTENTIAL IN RAT PANCREAS AT THE BURN SHOCK AND TOXEMIA STAGES OF BURN DISEASE - Netyukhailo, L.G.; Kharchenko, S.V. (World of Medicine and Biology, 2020)
The increase in general antitryptic activity was by 1.4 times higher for 1 day (at the stage of burn shock), while the total proteolytic activity decreased, compared to the respective parameters of the pancreas in the control group of rats under the conditions of burn disease. Then both indices decrease and remain reduced for 7 days. At the next stage of toxemia (on day 7), with a burn, the total antitryptic activity in the pancreas decreases by 1.6 times compared to the control animals. On the 7-th day, the total antitryptic activity in the pancreas decreases by 2. 2 times, compared to the 1-st day. Changes in proteolytic and antitryptic activity in the rat pancreas cause changes in proteinase-inhibitory potential at the stage of burn shock and the stage of toxemia in experimental burn disease. The proteinase-inhibitory potential of the rat pancreas on the 1-st day after the burn differs from this index value on the 7-th day.
Keywords: burn disease; pancreas; antitryptic activity; proteolytic activity